Austen Henry Layard at the remains of Nineveh: The everyday life of an archaeological expedition - A.A. Popova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The everyday life of research laboratories has been widely viewed as a promising avenue of historiographic studies concerning the accumulation, processing, and production of scholastic knowledge, which depends on many internal and external factors. Austen Henry Layard’s expedition is an unusual example of a historian’s laboratory. Most modern scholars agree that the excavations carried out by him date back to the prescientific stage in archeology development. At this stage, the theoretical and methodological foundations of this discipline were still undeveloped. Nevertheless, A.H. Layard’s contribution to the development of historical scholarship in general and Assyriology in particular was enormous. From that standpoint, the research performed at A.H. Layard’s laboratory, the process of obtaining and formalizing knowledge within it, and the factors that influenced its activity are of great interest. This article focuses on the factors of the everyday life of a laboratory scholar. Their influence on how the studies of the expedition’s materials were performed is analyzed. A.H. Layard’s main work “Nineveh and Its Remains” became a bestseller and drew the public’s attention to the Assyrian history and culture, as well as marked the beginning of the Assyriological research legitimization among scholars.